2019
DOI: 10.1002/ijc.32068
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cancer service centralisation on the radical treatment of men with high‐risk and locally advanced prostate cancer: A national cross‐sectional analysis in England

Abstract: In many countries, specialist cancer services are centralised to improve outcomes. We explored how centralisation affects the radical treatment of high‐risk and locally advanced prostate cancer in the English NHS. 79,085 patients diagnosed with high‐risk and locally advanced prostate cancer in England (April 2014 to March 2016) were identified in the National Prostate Cancer Audit database. Poisson models were used to estimate risk ratios (RR) for undergoing radical treatment by whether men were diagnosed at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…We also found that by using the CPG classification, the rates of surgery exceed radiotherapy only in men with CPG1 and CPG2 disease. Interestingly, in a prior publication, we showed an association between being diagnosed at a hospital with surgical services onsite and being more likely to receive surgery for their prostate cancer, than if these services were not available onsite [24].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…We also found that by using the CPG classification, the rates of surgery exceed radiotherapy only in men with CPG1 and CPG2 disease. Interestingly, in a prior publication, we showed an association between being diagnosed at a hospital with surgical services onsite and being more likely to receive surgery for their prostate cancer, than if these services were not available onsite [24].…”
Section: Discussionmentioning
confidence: 61%
“…The proportion of men diagnosed with CPG5 aged 70 or older was double that of those diagnosed with CPG1, indicating a clear progression of prostate cancer stage with age and that age at diagnosis is a major risk factor for aggressive disease. This observation highlights the complexity of the association of age and disease aggressiveness on the one hand and treatment selection on the other [23,24], given the clinical imperative to avoid early surgical complications in older patients and to reduce the need for later salvage treatments in patients with higher risk disease [25].…”
Section: Discussionmentioning
confidence: 93%
“…For more aggressive disease (CPG4 and 5) surgery was more commonly used in the US compared to radiotherapy in England, indicating that factors, such as healthcare organisation and funding, may be influencing treatment decisions. Treatment selection in both the US and England has been shown to be dependent on the services available (33,34). Mandatory multidisciplinary team (MDT) working for all newly-diagnosed patients with cancer and the use of joint urology/oncology clinics in England may affect patient selection and patient choice compared to the US.…”
Section: Discussionmentioning
confidence: 99%
“…There has already been a significant degree of centralisation of prostatectomy service in the UK following the publication of the national cancer plan in 2000 [24]. The benefits of any further centralisation must be weighed against its potential negative impacts on access to treatment for patients, out-ofpocket costs for patients' families, and the viability of urology services at non-centralised hospitals [1,25,26]. Moreover, training opportunities for junior healthcare professionals must be considered as part of any reorganisation.…”
Section: Discussionmentioning
confidence: 99%